1992
DOI: 10.1007/bf00142964
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between climatic change and the nomadic southward migrations in eastern Asia during historical times

Abstract: On the basis of data obtained from ancient Chinese chronicles, this study has established time series of southward and eastward migrations of the nomad people in the southern Mongolian grasslands and eastern central Asia from 190 B.C. to A.D. 1880 and found that there is a close relationship between climatic change and the migrations. We hypothesized that such a climate-migration relationship perhaps resulted from both livestock failure of the nomad people and crop failure of the Han Chinese during cold mid/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 16 publications
1
71
0
Order By: Relevance
“…4). These negative processes had been amplified by the minor cycle of individual behavior, notably the three instances of large-scale military actions to the northwest, southwest and Korea during the reign of Emperor Wanli, and its resulting heavy taxation on farmers (Fan and Cai, 1994). A recent study confirmed that climate change indeed impacted the key processes (military farm production, food and fiscal crises, peasant uprising, etc.)…”
Section: Climate Change and Social Processesmentioning
confidence: 98%
See 2 more Smart Citations
“…4). These negative processes had been amplified by the minor cycle of individual behavior, notably the three instances of large-scale military actions to the northwest, southwest and Korea during the reign of Emperor Wanli, and its resulting heavy taxation on farmers (Fan and Cai, 1994). A recent study confirmed that climate change indeed impacted the key processes (military farm production, food and fiscal crises, peasant uprising, etc.)…”
Section: Climate Change and Social Processesmentioning
confidence: 98%
“…This was particularly true for the period before the Yuan dynasty. Several large invasion events throughout history had brought destructive damage to the agrarian economy in the central plains, at least for the economy in northern China (Fu, 1981;Fang and Liu, 1992). From a macro-historic perspective, it may be one of the most important reasons contributing to stronger positive correlations between economic fluctuations and climatic indexes during the first millennium AD.…”
Section: Macro Mechanism For Climatic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…As climate altered, the Chinese and the nomadic people were either at peace or at war. The location of the farming-grazing transitional zone (hereafter FGTZ) shifted northwards or southwards as a result of the power balance between the Chinese and the nomadic people (Fang and Liu 1992) ( Fig. 5).…”
Section: Study Areamentioning
confidence: 99%
“…In contrast, those short-term extreme drought/flood events would abruptly cause adverse effects on a larger scale beyond the threshold that society can adapt. It has long been noted that large-scale peasant uprisings in Chinese history were usually accompanied by extreme drought events and induced famines due to short-term anomalous reductions in precipitation (Deng 1937). It is estimated that a shift from a relatively warm phase to a cold phase at the turn of the nineteenth century caused the social vulnerability to reach a critical level approximately 20 years earlier on the North China Plain during the late Qing Dynasty (Fang et al 2013).…”
Section: Potential Mechanism For Climatic Effectsmentioning
confidence: 99%